Elon Musk how the billionaire CEO of Spacex and Tesla is shaping our future - Vance, Ashlee (London Virgin Books, 2015)
Elon Musk, the entrepreneur and innovator behind SpaceX, Tesla, and SolarCity, sold one of his internet companies, PayPal, for $1.5 billion. Ashlee Vance captures the full spectacle and arc of the genius's life and work, from his tumultuous upbringing in South Africa and flight to the United States to his dramatic technical innovations and entrepreneurial pursuits. Vance uses Musk's story to explore one of the pressing questions of our age: can the nation of inventors and creators who led the modern world for a century still compete in an age of fierce global competition? He argues that Musk is an amalgam of legendary inventors and industrialists including Thomas Edison, Henry Ford, Howard Hughes, and Steve Jobs. More than any other entrepreneur today, Musk has dedicated his energies and his own vast fortune to inventing a future that is as rich and far-reaching as the visionaries of the golden age of science-fiction fantasy.
Elon's world -- Africa -- Canada -- Elon's first start-up -- PayPal mafia boss -- Mice in space -- All electric -- Pain, suffering and survival -- Liftoff -- The revenge of the electric car -- The unified field theory of Elon Musk.
Includes bibliographical references (pages 387-392)
Keywords: Tesla Motors--SpaceX (Firm)--PayPal (Firm); Businesspeople--United States--South Africa--Biography.; Inventors--Technological innovations--Economic aspects----Biography